Improving Alzheimer's Disease Detection for Speech Based on Feature Purification Network - Liu, Ning; Yuan, Zhenming; Tang, Qingfeng (Frontiers in Public Health, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disease involving the decline of cognitive ability with illness progresses. At present, the diagnosis of AD mainly depends on the interviews between patients and doctors, which is slow, expensive and subjective, so it is not a better solution to recognize AD using the currently available neuropsychological examinations and clinical diagnostic criteria. Recent study has indicated the potential of language analysis for AD diagnosis. In this study, we proposed a novel feature purification network which can improve the representation learning of Transformer model further. Though Transformer has made great progress in generating discriminative features because of its long-distance reasoning ability, there is still room for improvement. There exist many common features that are not indicative of any specific class, we rule out the influence of common features from traditional features extracted by Transformer encoder and can get more discriminative features for classification. We apply this method to improve Transformer’s performance on three public dementia datasets and get improved classification results markedly. Especially, the method on Pitt datasets gets state of the art (SOTA) result.